Urban children at risk of violence: A qualitative study of experiences of parents, teachers, and service providers of collaborative support - Nurjannah, Nurjannah; Oktari, Rina S.; Nisa, Haiyun; Viridanda, Wida Y.; Aidina, Wenny; Wang, Shr-Jie (Narra J, 2024)
Children who are at risk of involvement in violence need assistance from multisector agencies such as social services, law enforcement, health, and education. The aim of this study was to understand the perceptions and experiences of parents, teachers, and service providers (i.e., counselors, psychologists, paralegals, and social workers) on collaborative support for children at risk of violence in Banda Aceh, Indonesia. Twenty-four structured interviews were conducted with ten parents whose children were victims of sexual or physical abuse or were involved in substance abuse and theft and have received support from the Integrated Service Center for the Empowerment of Women and Children in Banda Aceh, Indonesia; ten service providers; and four teachers who either worked with the concerned children or knew them. Using a thematic analysis approach, the data was systematically coded and analyzed to identify important themes. Most parents who sought help or support from governmental agencies were referred by other service providers or recommended by relatives or friends. Parents hesitated to discuss their children’s problems with the teachers, worrying about stigma, particularly for sexual abuse victims. The school’s lack of collaboration with external agencies was consistent with the teacher’s claim that they seldom work with other agencies outside of school, resulting in a siloed system of care. It can be concluded that the biggest barrier to communication and coordination among parents, teachers, and service providers is the parents’ and service providers’ lack of willingness and confidence to work with teachers. Clear policies are needed to establish a cross-institutional linkage structure that promotes shared responsibilities.